-6m+m+10=35

Simple and best practice solution for -6m+m+10=35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6m+m+10=35 equation:


Simplifying
-6m + m + 10 = 35

Reorder the terms:
10 + -6m + m = 35

Combine like terms: -6m + m = -5m
10 + -5m = 35

Solving
10 + -5m = 35

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -5m = 35 + -10

Combine like terms: 10 + -10 = 0
0 + -5m = 35 + -10
-5m = 35 + -10

Combine like terms: 35 + -10 = 25
-5m = 25

Divide each side by '-5'.
m = -5

Simplifying
m = -5

See similar equations:

| 0.4x=7 | | (2/3)((7/8)+8x)-(3/8)=(5/8) | | 8=9x+8 | | 6+x=32 | | 6y-4=y+16 | | 4*(x-5)=3*(x+1)-15 | | 3-5+7=6-y | | 74869-54/6(706-8)-2*69= | | 2*(3+2x)=10 | | 5k+10=70 | | 13x+23=3x+303 | | 3.1a=16.43 | | 2x+4=x+5x-2x | | 4p+3q=14 | | Y=5/2x-20 | | 400+20x=680 | | 3+1=7x-24 | | 4x+7=9x+22-10x | | 5(0)+2y=-2 | | 6p+14=2p-10 | | 3x+5x=6+3 | | 5-3x=4x-16 | | (1/5)(2x-1)=7 | | 7/8(x-2)=119 | | 400+20x=468 | | m+8m-m+9= | | 26+a=2 | | 3/5x-4=7x | | (1/5)(2x-1)=5 | | 15-6x=5-10x | | -x+k=1/(x-1) | | 6p-14=2p-10 |

Equations solver categories